Description of Pregnant Woman with COVID-19 and Newborn Ooutcomes in Mitra Husada Hospital Pringsewu Years of 2020-2021 - Frizar Irmansyah; Irene Maria Elena; Veronica Agrippina Franesta (Jurnal MedScientiae, 2022)
COVID-19 is an infectious disease caused by Novel Coronavirus (nCoV). This virus easily infects the population of vulnerable groups and pregnant women are one of them. To prevent transmission, the procurement of large-scale social restrictions (PSBB) in Indonesia led to limited maternal and neonatal care health services. Fearing an increase in morbidity and mortality of mothers and newborns. Research on pregnancy and outcomes of newborns with COVID-19 is stil limited so the authors reviewed the picture of pregnant women with COVID-19 and the outcome of babies at Mitra Husada Pringsewu Hospital for the period 2020-2021.This study uses retrospective descriptive, cross sectional methods by tracing the medical record data of pregnant women with COVID-19 infection who gave birth at Mitra Husada Pringsewu Hospital. Most mothers are in the age range of 20-35 years and have given birth more than once. Births are predominantly by section caesarean section 70%, and only 23.3% of mothers have comorbid disease. Birth weight and APGAR scores are dominated by normal but 6.3% of babies have very poor grades of APGAR. Babies are born 62.5% aterm, and almost all babies show negative results of COVID-19.